2019
DOI: 10.1039/c8sc05164j
|View full text |Cite
|
Sign up to set email alerts
|

Primary α-tertiary amine synthesis via α-C–H functionalization

Abstract: A reactive ketimine intermediate was demonstrated to be intercepted by a variety of nucleophiles including organometallics and TMSCN.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 93 publications
0
43
0
2
Order By: Relevance
“…[4] The alkylation of a-C À Hb onds in aliphatic amines provides ap owerful alternative to established CÀNb ond-forming strategies, [5] but novel methods for the synthesis of a-tertiary amines via CÀHfunctionalisation are still urgently needed. [1] Given that primary alkyl amines offer the greatest potential for diversification, and are prevalent in pharmaceutical compound libraries (e.g., > 2700 non-benzylic primary amines in GSK'si nternal chemical inventory), methods for the a-CÀHa lkylation of this particular amine class could be transformative.D espite isolated reports of non-catalytic a-CÀHa lkylations of primary aliphatic amines, [6] including an amine dehydrogenation sequence with stoichiometric quinones, [7] catalytic protocols to directly access C-alkylated primary amines have proven elusive,e specially for nonbenzylic amines. [8] Indirect methods reliant on N-protection, catalytic CÀHa lkylation [9a,b] or arylation, [9b] and subsequent N-deprotection have been realised, but the triflamide or benzamide groups that are required suffer from harsh deprotection protocols.N otably,arecent study from Rovis, Schoenebeck, and co-workers showed that in situ N-protection of aliphatic primary amines with CO 2 enables acatalytic a-CÀHa lkylation process,l eading to g-lactam products ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…[4] The alkylation of a-C À Hb onds in aliphatic amines provides ap owerful alternative to established CÀNb ond-forming strategies, [5] but novel methods for the synthesis of a-tertiary amines via CÀHfunctionalisation are still urgently needed. [1] Given that primary alkyl amines offer the greatest potential for diversification, and are prevalent in pharmaceutical compound libraries (e.g., > 2700 non-benzylic primary amines in GSK'si nternal chemical inventory), methods for the a-CÀHa lkylation of this particular amine class could be transformative.D espite isolated reports of non-catalytic a-CÀHa lkylations of primary aliphatic amines, [6] including an amine dehydrogenation sequence with stoichiometric quinones, [7] catalytic protocols to directly access C-alkylated primary amines have proven elusive,e specially for nonbenzylic amines. [8] Indirect methods reliant on N-protection, catalytic CÀHa lkylation [9a,b] or arylation, [9b] and subsequent N-deprotection have been realised, but the triflamide or benzamide groups that are required suffer from harsh deprotection protocols.N otably,arecent study from Rovis, Schoenebeck, and co-workers showed that in situ N-protection of aliphatic primary amines with CO 2 enables acatalytic a-CÀHa lkylation process,l eading to g-lactam products ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Dixon and co‐workers reported an elegant strategy for the synthesis of primary α‐tertiary amines by the α‐C−H functionalisation of α‐secondary amines (Scheme 12 A). [33] This bio‐inspired method proceeds through the reaction of quinone with primary amines to generate ketimine intermediates in situ, which can readily react with C‐centred nucleophiles. The versatility of this transformation was demonstrated by its broad scope.…”
Section: De Novo Synthesismentioning
confidence: 99%
“…[32,33] As such, there is a broad interest in developing these motifs using direct functionalization of CÀ H bonds present next to the nitrogen atom. Recently, transition metal-free strategies such as Nlithiation mediated imine formation of cyclic amines followed by reaction with organometallic nucleophiles [34] and quinone mediated ketimine formation from primary amines followed by in situ oxidation [35] have emerged for α-functionalization of amines among others. [36] Although transition metal-free protocols offer a good alternative, they often show limited scope towards number of functionalization.…”
Section: α-Cà H Activation and Functionalization Of Aminesmentioning
confidence: 99%
“…Several CÀ H functionalizations have been reported in the presence of N-linked DGs, which typically possess Lewis basic nitrogen or sulfur able to coordinate to the metal and perform metallation at the α-CÀ H bond. [35,37] Various low and high valent metals such as Rh, Ru, Ni, Pd, and Ir have been used for the metallation [20] followed by functionalization/derivatization such as arylation, alkylation, and oxidation.…”
Section: α-Cà H Activation and Functionalization Of Aminesmentioning
confidence: 99%